Innovative mechanism for building leadership skills and competence among youths in educational setting: the outcome of a three-phased experiment (2018)
This study reported the outcome of a three-phased experiment on building leadership skills and competence among undergraduate students at the Department of Aduh Education, University of Ibadan, Nigeria. The basic objective of the experiment was to find-out if students, given the leadership and authority figure to facilitate leaching, would develop and acquire leadership qualities and skills. The experiment was carried out in three phases: The first phase involved 25 students who registered for a course ADE 207 (Principles and Practice of Adult Education) in first semester, 2015/16 academic year. The students were allocated each topic in the outline to prepare and facilitate the leaching on rotational basis. The second phase took place in second semester 2015/2016 academic year with a course ADE 208 (Cost, Budgeting and Financing Adult Education Programs) and the third phase took place in first semester 2016/2017 academic year with ADE 303 (Current issues and Problems in Adult Education). During the methodological processes, other students were asked to secretly rate their colleagues, who assumed the lectureship position, using these rating scores: 1-2 (Poor). 3-4 (Fair), 5-6 (Good), 7-8 (Very Good), and 9-10 (Excellent) on identified parameters. The outcome of the experiments showed that the performance rating scores of all the students, at the first phase, was poor between (1-2) in most of the parameters. However, at the second phase, the rating scores had improved to between (5-6) marks while at the third phase, the performance rating had improved to between (7-8) marks. Two implications were derivable from this experiment: firstly, schools’ curriculum and teaching methodologies must be re-structured to give students, the future leaders, the opportunity to develop their leadership skills and competence right from the school: and secondly, leadership skills can be acquired if people are given continuous exposures and opportunities